Contribuição ao estudo epidemiológico demográfico das neoplasias malignas da cavidade bucal no Estado da Paraíba - Paiva, Marcos Antônio Farias de (2000)
This epidemiologic study, exploratory and descriptive by its nature, aimed at checking the predominance of malign neoplasias in the oral cavity, in the state of Paraíba , through the analysis held at Hospital Dr. Napoleão Laureano in João Pessoa-Pb., involving 1237 patients records, from 1988 to 1999. The results revealed the predominance of carcinoma with scaly cells, amounting to 61,8%, the highest incidence comprised people from 61 to 80 years old, 52,3%, the most affected anatomic regions were the tongue, with 27,3% and the lower lip, whit 13,5% out of the total analysed. To achieve these results, some geographic classifications were taken into consideration – the Litotoral region displayed a highest incidence of cases, with 39,9%, Agreste, with 27,2%, Backwoods ( Sertão ) with 25,9%, Borborema, with 4.9% and 2,1% stemming from near towns. Out of the total cases affecting the tongue, 44,4 were from the Littoral, and the ones which affected the upper lip, 42,4% were from Backwoods ( Sertão ) and the regions featuring the hightest incidence as to number of inhabitants were the Littoral, with 39 cases / 100.000 inhabitants and the Backwoods ( Sertão) with 37 cases / 100.000 inhabitants.